Clever Algorithms NatureInspired Programming Recipes - Brownlee, Jason (lulu.com, 2012)
This book provides a handbook of algorithmic recipes from the fields of Metaheuristics, Biologically Inspired Computation and Computational Intelligence that have been described in a complete, consistent, and centralized manner.